Conflict of interest statements in biomedical publications. A study of four Spanish health care journals - Roig, Francesc; Borrego, Ángel (Acta Bioethica, 2017)
Disclosure of financial relationships between researchers and pharmaceutical companies is seen as an essential step in the management of potential conflicts of interest. The objective of the study was to evaluate the frequency of conflicts of interest disclosure in four Spanish biomedical journals: Atención Primaria, Medicina Clínica, Revista Clínica Española and Revista Española de Cardiología. Publications qualified as “Editorial”, “Original Article”, “Consensus Document”, “Review” and “Special article” in 2012 were analyzed. Of 412 articles, 315 (76%) had a conflict of interest statement. By journal, 73% of the articles in Atención Primaria, 68% in Medicina Clínica, 60% in Revista Clínica Española and 100% in Revista Española de Cardiología had disclosure of conflicts of interest. Only 12% of disclosures reported activities, while the rest maintains “No conflict of interest”. In addition to a considerable variability in the frequency of conflicts of interest disclosure, the presence of activities disclosed is low. It would be necessary to improve the consistency and transparency of the policy declaration of conflicts of interest.